New ski binding design is required to reduce the incidence of serious knee injuries seen in Alpine skiing. A call for proactive intervention - Howard, M. (Asia Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2018)
Introduction & Aims: Injury to the Anterior Cruciate Ligament (ACL) is overrepresented in alpine skiing injuries and is 365 times higher compared to general population risk. Methods of ACL injury in skiing are known yet technology that could respond to this and protect the ACL have not been commercially developed. The aim of this study is to highlight injury methods and ski binding technology that may protect the ACL.